Analisis Fluktuasi Harga Pangan Di Kabupaten Lombok Timur - Danang Prio Utomo (Universitas Hamzanwadi, 2022)
This study aims to determine how the fluctuations are in food prices of East Lombok Regency. Where this study covers 10 food commodities including: rice, chicken meat, beef, chicken eggs, shallots, garlic, red chilies, cayenne pepper, cooking oil, and sugar. The respondent was determined by using a purposive technique, which was in certain considerations. While, as being the consideration in determining the respondent, the participants who are responsible or who have a role in providing information about the data needed in this study through interviews were 19 people of food traders in Aikmel Public Market. The data used in this study was time series data in 2020 and analyzed using descriptive analysis in the form of linear trend analysis. The results of this study indicated that in 2020 all food commodities, including rice, chicken meat, beef, chicken eggs, shallots, garlic, red chilies, cayenne pepper, cooking oil and sugar, experienced price fluctuations. These fluctuations were caused by weather and season factor, demand, total stock, and raw material prices. Meanwhile, food price trends, rice, beef, and cooking oil commodities experienced an upward trend, while chicken meat, chicken eggs, shallots, garlic, red chili, cayenne pepper, and sugar commodities experienced a decreasing trend